Aksara digital Banjardowo: UMKM lokal menuju desa wisata cerdas melalui KKN di Dukuh Banjardowo, Klaten - Hidayah, Faatikhah Arrum Nur; Fakta, Hindiana Bela; Noviana, Sholiqah Risma Tri; Sholihah, Fadhilah Umi; Romadhona, Manal Rizqulloh; Amborowati, Mayank Noverly; Syahputri, Rezyana Budi (Tintamas: Jurnal Pengabdian Indonesia Emas, 2025)
Community service through the Community Service Program (KKN) is one form of student contribution to addressing community problems. Community service through the Community Service Learning Programme (KKN) in Banjardowo Village aims to increase awareness and utilisation of digital technology for Micro, Small, and Medium Enterprises (MSMEs). The lack of digital information about important locations in Banjardowo Village, such as MSMEs and tile manufacturing sites, has become an obstacle to disseminating marketing information and providing access to the broader community. Through the Community Service Program (KKN), the service team conducted digital mapping using Google Maps to introduce and facilitate access to MSME locations, especially roof tile production sites, and to create business image boards for culinary MSMEs in Banjardowo Village. Students also provided education to children on instilling Islamic values, insights into the village's potential, and the importance of Clean and Healthy Living Behaviour (PHBS). The results of this activity are expected to increase the visibility and competitiveness of local MSMEs and support the development of Banjardowo Village as a smart tourist village.